Solriamfetol impurities: Synthesis, characterization, and analytical method (UPLC-UV) validation - Nafisah Al-Rifai; Anas Alshishani; Fouad Darras; Ola Taha; Shereen Abu-Jalloud; Lena Shaghlil; Yousef Al-Ebini (Elsevier, 2023)
Given that impurities may affect the quality and safety of drug products, impurity identification and profiling is an integral part of drug quality control and is particularly important for newly developed medications such as solriamfetol, which is used to treat excessive daytime sleepiness. Although the high-performance liquid chromatography analysis of commercial solriamfetol has revealed the presence of several impurities, their synthesis, structure elucidation, and chromatographic determination have not been reported yet. To bridge this gap, we herein identified, synthesized, and isolated eight process-related solriamfetol impurities, characterized them using spectroscopic and chromatographic techniques, and proposed plausible mechanisms of their formation. Moreover, we developed and validated a prompt impurity analysis method based on ultrahigh-performance liquid chromatography with UV detection, revealing that its selectivity, linearity, accuracy, precision, and quantitation limit meet the acceptance criteria of method validation stipulated by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use. Thus, the developed method was concluded to be suitable for the routine analysis of solriamfetol substances.